The usability of i-suyyah: a mobile tourism application for Arab tourists in Malaysia - Wan Ab Aziz Wan Daud (Tanjung Malim, 2021)
The usability of i-suyyah: a mobile tourism application for Arab tourists in Malaysia by Wan Ab Aziz Wan Daud